Absolutizem in trg - Spruk, Jure (Teorija in praksa, 2018)
In the paper, the author explains the connection between perceiving secular power, as presented in the texts of a founder of the protestant reformation Martin Luther, and his critique of the commercialisation of sin by the medieval Christian Church and perception of the Church as a papal monarchy. Luther defines secular power as a God-given institution which accepts providing order and stability in the community as its mission, thus placing her above any other authority on earth. An ideal secular ruler turns out to be a pious Christian ruler whose will has the power of the law. Secular power must act with unlimited authorisation when the human body and property are in question because, in the opposite case, it would not have the capacity to fulfil the mission of an unrelenting tamer of human low passions which stem from the original sin of the first parents. Political obligation binds a true Christian to obedience; in the case of the unjust acting of secular power, passive resistance is commanded. Luther's absolutism emerges as a premodern bulwark of protestant religion which finds shelter in the idea of state religion. The end of the monopoly of the medieval Church coincided with the idea of the absolutist governance of secular power. Absolutism received a keen image of a subject - a god-fearing man who gives his body and property to the unlimited governance of the monarch.
Keywords: Absolutism; Absolutizem; Cerkev; Church; Luther, Martin; posvetna oblast